Flow Response to Large-Scale Topography: the Greenland Tip Jet - Doyle, James D.; Shapiro, Melvyn A. (1999)
Numerical model simulations of idealized and observed flows are used to investigate the dynamics of low-level jet streams that form in stratified flow downstream of the vertex of large elliptical barriers such as the southern tip of Greenland, hereafter referred to as "tip jets". The tip jet dynamics are governed by conservation of Bernouli function as parcels accelerate down the pressure gradient during orographic descent. In some circumstances, the Greenland tip jet is influenced by baroclinic effects such as differential horizontal (cross-stream) thermal advection and/or vertical shear. In contrast, in the barotropic situation upstream flow is diverted around and over the obstacle into laminar (Bernouli conservation) and turbulent (Bernouli deficit) regimes, respectively. In both situations, a downstream geostrophic balance is achieved, characterized by baroclinicity and vertical shear associated with the surface-based tip-jet front. The strength of the tip-jet is most sensitive to changes in the basic state dimensionless mountain height (Nh/U) and Rossby number, underscoring the importance of the orographic deflection of airstreams and Lagrangian accelerations on the slope. Enhanced surface-based forcing of the ocean circulation occurs in the region of the tip jet core through large air-sea energy exchange (upward surface-heat fluxes greater than 800W m(exp -2)), and at the tip jet flank through localized surface stress forcing. Published in Tellus, v51A p728-748, 1999. Sponsored in part by ONR.